As copas do mundo de futebol de 1934 e 1938 por meio dos jornais de São Paulo e Rio de Janeiro - Carrara, Cibelle Cordeiro [UNESP] (2014)
Football arrived in Brazil as a high class sport and bit by bit it got to all social classes. There were a lot of discussions about it during the three Republican decades when it was trought about racial matters, which were spreading at the time, as well as its good side for Physical Education. It became the most popular sport in the country in the 1930´s and it was recognized a professional sport in 1933. The mass communication took an important part on it, during its establishing period, with specialized sections on newspaper and forecasting match on the radio which was possible because of adverting being allowed early in that decade. It was then that the World Cup competitions started and Brazil is the only country that took part in all its editions. The aim of this essay is to analyze the competitions that happened in the so called first Vargas government in 1934 e 1938. Although they both happened at close dates, the historic contexts were quite different: the first one was when the democratic rules were reestablished and the other one during the “Estado Novo”. Although Brazil did not win any of those competitions, the 1938 World Cup mobilized the authorities much more than the previous one, it got to on enormous dimension. Because of this each of the time when they happened were analyzed due to the importance of the historical circumstances to understand the differences between them. The used sources were the most important newspaper in Rio de Janeiro (Correio da Manhã) and in São Paulo (O Estado de S. Paulo e o Diário de S. Paulo), because with them it is possible to follow the disputes, values and ideas at the time. It is important to notice that these periodic sources are seen as opinion formation, showing a vision of the world, and more, acting or being used as political instrument